Designing the “FIT-TRACK” Website as a Fitness Programme Medium for PKP-PK Personnel at the Airport - KOMALASARI, YETI; Andra Dwi Nugraha; Zusnita Hermala; Yani Yudha Wirawan (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2025)
The study aims to design and develop a website-based learning medium called FIT-TRACK, which functions as a physical fitness program for PKP-PK personnel at Sultan Mahmud Badaruddin II Airport in Palembang. This website was developed as a solution to the lack of structured fitness programs and digital media that support independent training in the PKP-PK unit. The research method used a Research and Development (R&D) approach with the ADDIE model. Data collection techniques included observation, interviews, and questionnaires. Validation was carried out by two expert validators, namely material experts and media experts, and user feasibility testing was carried out by PKP-PK personnel. The results showed that FIT-TRACK was developed with an interactive and simple design using the Google Sites platform, with features such as: home (beep test, push-ups, sit-ups, planking), weekly schedule, metronome, and fitness assessment. The subject matter expert feasibility test scored 93.66% in the highly feasible category, while the media expert scored 90.65% in the highly feasible category. The respondent feasibility test on 22 PKP-PK personnel scored 60.9% strongly agree and 39.1% agree that the FIT-TRACK website is effective and easy to use. During the evaluation phase, it was recommended to develop the metronome feature and additional materials in accordance with NFPA 1583 standards. The success of the FIT-TRACK website has the potential to become a structured, flexible fitness program that supports personnel's physical readiness for emergency tasks.